Step‐Edge‐Induced Patterning and Orientation Control of Crystalline Organic Semiconductor Films. Issue 8 (12th February 2023) - Wang, Zhifang; Martin‐Jimenez, Daniel; Zhong, Qigang; Ebeling, Daniel; Schirmeisen, Andre; Wang, Hong; Wang, Wenchong; Chi, Lifeng
Abstract: Orientation control over micropatterned crystalline organic semiconductor film is crucial to achieve high device performance with small variation in organic electronics. Here, using Au patterned SiO2 substrates, a method is reported to realize high‐resolution patterning and orientation control of crystalline organic thin films simultaneously. The vacuum deposited N, N ‐dioctyl‐3, 4, 9, 10‐perylene tetracarboxylic diimide (PTCDI‐C8 ) molecules can selectively diffuse to and nucleate on prepatterned Au stripes, resulting in patterned crystalline films with a preferential orientation distribution. Scanning tunneling microscope and high‐resolution atomic force microscope images reveal that the PTCDI‐C8 molecules first assemble on Au with perylene diimide cores in a laying down configuration, providing nucleation sites at the step edges for directional growth along the a ‐axis of the molecule crystal. Subsequent deposition of molecules leads to orientated crystalline films growth due to the π packing of the perylene diimide cores, resulting in orientation control on micropatterned crystalline films. The finding provides a new strategy to grow oriented crystalline films for high device performance uniformity. Abstract : High‐resolution patterning and orientation control of the crystalline organic semiconductor films can be achieved simultaneously by utilizing Au‐step‐edge to induce molecular packing orientation.